The Association between Proton Pump Inhibitors and Myocardial Infarction: what do FDA data tell us? - Tan, Jiun Ming; Sim, Tin Fei; Parsons, Richard; Lee, Ya Ping (Medknow Publications, 2019)
Objective: There is limited and conflicting evidence on the association between proton pump inhibitors (PPIs) and myocardial infarction (MI). This study aims to examine the occurrence of MI associated with PPI use from the Food and Drug Administration (FDA) Adverse Event Reporting System database.